Simple Redo Proximal Thoracic Aortic Surgery with Peripheral Cardiopulmonary Bypass and Minimal Dissection - Uchida, Tetsuro (Ann Thorac Cardiovasc Surg, 2019)
Reoperations on the proximal thoracic aorta are increasingly observed after previous aortic or cardiac operations. Redo proximal aortic surgery remains challenging with an increased mortality compared to first-time operations. For a successful redo proximal aortic surgery in a patient with complex pathological conditions, the surgical procedure and cardiopulmonary bypass (CPB) should be simplified as much as possible. Herein, we report our experience of proximal aortic reoperations in which the strategy consisted of an axillo-axillary (jugular) and a femoro-femoral CPB in combination with minimal dissection of surgical adhesions. Satisfactory full-flow CPB was achieved with peripheral cannulations and the aid of vacuum-assisted venous drainage. A suitable surgical view of the proximal aorta was obtained without dissection of the heart. There was no operative mortality and the peripheral CPB was well managed without technical problems. We consider that the proposed strategy makes proximal aortic reoperations safe and simple.